The Outcomes of Lower Eyelid Reconstruction after Carcinoma Excision: Case Series - Deny Wiryulisda; Hendriati (HM Publisher, 2022)
Introduction: Eyelid reconstruction after excision of carcinoma can be challenging due to the dynamic movement and anatomy of the eyelid. Flap and graft are choices of techniques to fill and repair broad eyelid defects. Significant lower eyelid defects can typically be closed using skin flaps and grafts to substantiate the posterior lamella. This study aims to describe three cases with lower eyelid reconstruction and evaluate the outcome of the surgery. Case presentation: There are three cases of lower eyelid reconstruction reported in this study. In cases 1 and 2, the surgical procedures need graft for posterior lamellae reconstruction. In case 3, the reconstruction process only required a rotational flap. All patients are in good aesthetic and functional outcomes. Conclusion: Combination of skin flap (transposition and rotational flap) and graft (oral mucosa and transconjunctival) and only rotational flap can achieve favorable functional and aesthetic outcomes in wide excision of carcinoma.